Bureaucratic Responsiveness to LGBT Americans. Issue 3 (3rd December 2019) - Lowande, Kenneth; Proctor, Andrew
Abstract: Marriage rights were extended to same‐sex couples in the United States in 2015. However, anecdotes of bureaucratic noncompliance (in the form of bias or denial of license issuance) raise the possibility that de jure marriage equality has not led to equality in practice. We investigate this by conducting a nationwide audit experiment of local‐level marriage license–granting officials in the United States. These officials vary in the constituencies they serve, as well as how they are selected, allowing us to evaluate long‐standing hypotheses about bureaucratic responsiveness. Overall, we find no evidence of systematic discrimination against same‐sex couples—regardless of responsiveness measure, institutions, ideology, or prior state legal history. We find, however, that among same‐sex couples, officials tended to be more responsive to lesbian couples. In contrast to evidence in other areas of service provision, such as policing and federal assistance programs, we find bureaucrats tasked with provision of marriage services show little evidence of discrimination.